Evaluation of the efficiency of the management plan for the zone of damping (Research, Society and Development, 2021)
The most engaged and concerned society with environmental issues started to discuss, demand, and encourage measures that would reduce the environmental impacts on ecosystems leading to the creation of Conservation Units (UC's) to protect and conserve the areas that were submitted degradation processes and were representative of ecosystems and biomes. Therefore, the objective was to carry out a descriptive analysis of the importance and effectiveness of the Management Plan for Buffer Zones of Conservation Units through research in legislation and technical documents that address this issue. The buffer zone covers the surroundings of a conservation unit where human activities are subject to specific rules and restrictions to minimize negative impacts on the conserved area. The buffer zone, although it does not belong to the Conservation Units, excels in protecting the riparian forest; landscape preservation; promoting environmental education and improving the lives of the surrounding population; urbanization control; and planning and consolidation of appropriate uses for the management plan the conservation units. The establishment of buffer zones must always respect the needs of each conservation unit and surrounding communities. Thus, public policies are needed that effectively promote management plans in the Conservation Units with the direct participation of the Buffer Zones community. The Conservation Units with a management plan have positive effects on the Buffer Zones. However, concrete information regarding the efficiency of management plans in the Conservation Units and Buffer Zones is still scarce.